2018
DOI: 10.1136/bcr-2018-226096
|View full text |Cite
|
Sign up to set email alerts
|

Hypermucoviscous capsular 1 (K1) serotypeKlebsiella pneumoniaenecrotising fasciitis and metastatic endophthalmitis

Abstract: A 48-year-old man presented with a non-healing wound on his left foot after stepping on a nail. He self-medicated with amoxicillin, but the wound progressed prompting consult. On examination, his left foot was diffusely swollen with surrounding erythema, areas of gangrene, foul-smelling purulent discharge and subcutaneous emphysema. He was managed as a case of necrotising fasciitis and underwent emergent amputation. Three days after amputation, he developed a sudden and progressive blurring of vision, swelling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…The K1 serotype of K pneumoniae is the major serotype that induces deep abscesses. [4,11,12] Invasive infection caused by K pneumoniae is common in immunosuppressed patients, but it could also be observed in some immunocompetent patients. It was reported that prevalence of K pneumoniae in healthy adults was 75%, with a high prevalence (23%) of serotype K1 or K2 isolates in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…The K1 serotype of K pneumoniae is the major serotype that induces deep abscesses. [4,11,12] Invasive infection caused by K pneumoniae is common in immunosuppressed patients, but it could also be observed in some immunocompetent patients. It was reported that prevalence of K pneumoniae in healthy adults was 75%, with a high prevalence (23%) of serotype K1 or K2 isolates in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…5 Thus, K. pneumoniae is more virulent and aggressive in Asia, and Asian populations are more likely to develop IKPLAS. Chiu et al 6 reported a clinical case of K. pneumoniae invasive syndrome caused by a non-healing wound after foot trauma. The middle-aged male patient was treated with antibiotics (piperacillin/tazobactam 4.5 g q8h, vancomycin 1 g q12h) and emergency double-calf amputation to control the infectious foci of necrotizing fasciitis after admission.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous endophthalmitis occurs when the infecting organisms directly enter the eye, while endogenous endophthalmitis results from infectious agent hematogenous seeding of the eye. In the literature, septic metastatic endophthalmitis may develop from distant NF of a lower extremity infected by Klebsiella pneumoniae [ 9 ]. Severe infections, such as liver abscesses and bacteremia, can also cause endogenous endophthalmitis concurrent with orbital cellulitis or NF of the leg [ 10 , 11 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%